Impacts of Private and Public Physical Capital Accumulation on Economic Growth of Ethiopia - Hayu Gemechu; Leta Sera; Tekilu Tadesse (Journal of Science and Inclusive Development, 2021)
The main objective of this research was to examine the impacts of private and public physical capital accumulations on economic growth in Ethiopia for the period ranging from 1974/75- 2017/18 by using Auto Regressive Distributed Lag (ARDL) Approach to Co-integration and Vector Error Correction Model. The result showed that real private capital accumulation had statistically insignificant impact while public capital accumulation had negative and statistically significant impact on economic growth of Ethiopia in the long -run. The result also revealed that human capital and labor force had positive and statistically significant impact while trade openness, macroeconomic instability and foreign aid had negative and statistically significant impact in determining economic growth of Ethiopia in the long- run. In addition, in the short -run private and public capital stocks had negative and statistically significant impact on economic growth of Ethiopia at first lag while human capital, labor force, trade openness, macroeconomic instability and foreign aid had positive and significant impact on economic growth of Ethiopia with lag. Overall, the policy implication of this study is that, given the long -run insignificant impact of private capital and negative significant impact of public capital stocks on economic growth, it is recommendable to reduce public capital investment in different sector investments rather better to encourage private sector participation on economic activities in Ethiopia.